Desenvolvimento de analisadores automáticos em fluxo para o monitoramento de analitos de interesse farmacêutico utilizando microdispositivo LTCC e um minifotômetro Labmade - Pessoa Neto, Osmundo Dantas (Universidade Federal de São Carlos, 2011)
The objective of this study was to develop automatic flow analyzers for the determination of pharmaceutical analytes using a micro-device based on LTCC (Low Temperature Co-fired Ceramics) and a mini-photometer as the detection system. To perform this task, the following devices were developed: 1) A mini-photometer based on RGB-LED (Red Green Blue- Light Emitting Diode) which wavelengths of maximum emission are 465, 525, and 640 nm, respectively, was used as the radiation source. A photodiode (PD) was used as a detector; 2) An optical cell for flowing analysis. A software was developed in graphic language using LabView® 7.0 in order to control and acquire analytical data. The mini-photometer for flowing analysis and software were developed for the determination of N-acetylcysteine (NAC), captopril (CAP), adrenaline (DNA), dopamine (DPN) and ascorbic acid (AAc) in pharmaceutical formulations. First, the mini-photometer was developed and used as a photometric detector. Then, a labmade valve actuator (VA) connected to a computer interface for data acquisition (National Instruments USB 6008) was used to switch on/off the solenoid valves. This interface also enabled to control the mini-photometer as well as the acquisition and processing of transient signals generated in the LTCC. In all determinations, the miniphotometer, the LTCC and the flow system with multicommutation employing threeway solenoid valves were used, except for NAC and CAP where an analyzer with manual injector was used. Solid-phase reactors were also used due to lower reagents consumption. The results from the developed system were compared with reference and validated methods (found in the literature) and there were no significant differences at 95% confidence level. The developed system with LTCC employs low volume of reagents and samples and can be used to determine several analytes in different matrices. applied in any other used (due to), along with a system of universal (able to be applied in any other application in flow) were other good features of this developed system. The good stability and sensibility of the developed mini-photometer (4 x 4 cm) enabled an adequate performance during the determinations.
Development of flow analyzers for the determination of pharmaceutical analytes using a LTCC micro-device and a miniphotometer used as detection system
Keywords: Química analítica; LTCC; Fármacos; Sistema em fluxo; CIENCIAS EXATAS E DA TERRA::QUIMICA